Modified-likelihood estimation of fixed-effect models for dyadic data - Koen Jochmans (SERIEs - Journal of the Spanish Economic Association, 2023)
We consider point estimation and inference based on modifications of the profile likelihood in models for dyadic interactions between n agents featuring agent-specific parameters. The maximum-likelihood estimator of such models has bias and standard deviation of order n-1 and so is asymptotically biased. Estimation based on modified likelihoods leads to estimators that are asymptotically unbiased and likelihood ratio tests that exhibit correct size.
Keywords: C23; 330; Asymptotic bias; Dyadic data; Fixed effects; Undirected random graph